Factors Influencing Ledge Formation and Its Management in Endodontics - Ramachandran Tamilselvi1 , Veronica Aruna Kumari2 , Ilango Porkodi3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Endodontic treatment can be predictable, successful, and relatively easy to perform if every individualstep is performed appropriately. Hasty mechanical and chemical manipulation of the root canal system canlead to procedural error. Procedural accidents during endodontic treatment occurs either due to inadequateattention to the details. Removal of canal wall structure on the outside curve in the apical half of the canaldue to the tendency of files to restore themselves to their original linear shape during canal preparation maylead to ledge formation and possible perforation.